Rapid design of a screw drive in-pipe robot based on parameterized simulation technology. (July 2019) - Li, Te; Liu, Kuo; Liu, Haibo; Cui, Xuewen; Li, Bin; Wang, Yongqing
The screw drive in-pipe robot is a type of effective intelligent equipment for inspecting pipeline failure. In-pipe robots have a wide range of design parameters due to varied pipe types and application conditions. Experiential or theoretical design means cannot ensure the validity and success rate, which leads to the increase in production cost and cycle. Therefore, in order to solve the rapid design problem of screw drive in-pipe robots, a parameterized simulation system based on ADAMS secondary development technology and a simple design strategy is proposed. Firstly, the motion principles of screw drive in-pipe robots are analyzed to establish a generalized design model. Then, the key parameters of the geometric structure are extracted and associated, which work as the input variables to design the robotic model. Then the general parameterized simulation system is established based on the CMD language of ADAMS simulation software. Finally, a simple design strategy is proposed and a design application case for pipeline diameter of 225 mm is studied. The results show that the parameterized simulation system can build and test varied screw drive in-pipe robot models quickly by only inputting some design parameters. The proposed design system and strategy can help realize the production of a screw drive in-pipe robot rapidly.